Molecular microbiology : diagnostic principles and practice - Persing, David H. (ASM Press, 2011)
provides complete coverage of the principles and applications of molecular microbiology as they pertain to infectious diseases; summarizes the basic scientific theory underlying molecular diagnostics; reviews proven applications of molecular diagnostic techniques for the diagnosis of infectious diseases